Performance Optimization and Water-Saving Retrofit of the Sealing Water Cooling System for Unit 1 Feedwater Pumps at PLTU IPP Sumsel - Wang Zhiliang (Riviera Publishing, 2025)
During the operation of Unit 1 at PLTU Sumsel 5, the feedwater pump seal water cooler experienced issues such as poor cooling performance, low heat exchange efficiency, and high-water consumption, leading to elevated equipment operating temperatures, increased energy consumption, and wastage of water resources. To enhance the operational economy and reliability of the equipment, an optimization upgrade was carried out on the existing seal water cooling system during the unit's annual maintenance. The retrofit plan involved replacing the originally used demineralized water-cooling source with chilled water from the HVAC system as the working medium, while retaining the demineralized water system as a backup source. After the upgrade, the system's cooling performance improved significantly, with a reduction of approximately 65% in cooling water consumption. This achievement demonstrates dual benefits of water conservation and reduced energy consumption, while also improving operational efficiency. The project provides replicable engineering experience for optimizing auxiliary systems in similar units.